Brazil’s Belo Monte Dam: Lessons of an Amazonian resource struggle - Fearnside, Philip Martin (DIE ERDE – Journal of the Geographical Society of Berlin, 2017)
The struggle to stop Brazil’s Belo Monte Dam, whose reservoir was filled in December 2015, has lessons for other resource struggles in Amazonia and beyond. Among the impediments that failed to halt the dam were the resistance efforts of both indigenous and non-indigenous victims of the dam’s impacts, as well as the nongovernmental organizations and other actors supporting their cause. The pro-dam side had massive political and financial support from the top levels of the Brazilian government, including vigorous involvement of the country’s president. At the same time, achievements of the anti-dam side, particularly the local grassroots organizations, have provided inspiration for resource struggles elsewhere (although the victories of the resistance are significantly less definitive than was thought by many at the time).